PENGGUNAAN MAZE NUMERIK TERHADAP PENINGKATAN KEMAMPUAN MENGENAL ANGKA MURID AUTIS KELAS II DI SLB NEGERI 1 KOTA BIMA - Suciramdani; Bastiana; Zulfitrah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem studied in this study is the low number recognition ability of autistic students, characterized by difficulties in matching numbers, showing numbers, and naming numbers according to the given number symbols. The purpose of this study was to determine the improvement in number recognition ability through the use of numerical maze media in second-grade autistic students at SLB Negeri 1 Bima City. The research approach used was a quantitative approach with a descriptive type of research that focused on changes in ability before and after the use of numerical maze media. The subject of this study was a second-grade autistic student with the initials FYAA who had low number recognition ability. The data collection technique used was a performance test adapted to the indicators of number recognition ability, namely matching numbers, showing numbers, and naming numbers. Data analysis was carried out by comparing the test results before and after the use of numerical maze media and describing the test results. The conclusion of this study is (1) the ability to recognize numbers in autistic students before the use of numerical maze media is in the unable category with a value of 10, (2) the ability to recognize numbers in autistic students after the use of numerical maze media is in the very able category with a value of 90, and (3) there is an increase in the ability to recognize numbers in autistic students through the use of numerical maze media from the unable category to very able. This study shows that the use of numerical maze media can improve the ability to recognize numbers in autistic students in class II at SLB Negeri 1 Kota Bima.